CHARACTERISTICS FISH OIL FROM BELLY FAT PATIN (Pangasius hypophthalmus) IS REFINNED USING BENTONITE - Lorde Sembiring; Mirna Ilza; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Catfish processing (Pangasius hypophthalmus) produces byproducts of belly fat containing unsaturated fatty acids, polyunsaturated fatty acids (PUFAs) consisting of linoleic, linolenic, EPA, and DHA are the essential fatty acids the body needs to maintain health. Utilizing belly fat catfish can be processed into crude fish oil. Raw fish oil is purified to increase its economic value. Purification of fish oil usually uses absorbent one of them bentonite. Bentonite is used in the process of purifying oil as a pallor due to its high montmoriloni content. These research was conducted to study the effect of bentonite use (1, 4, 7%) on the characteristics of refined catfish oil. The design used completely non factorial randomized design. Bentonite addition treatment factor used A1 (1%), A2 (4%), A3 (7%) and repeated as many as 3 repetitions. The results showed that bentonite had significant effect on fat content, peroxide number, anisidin and total oxidation number. The use of 7% bentonite decreased content of fat, peroxide number, anisidine, peroxidants and total oxidation respecively from 1.72 to 0.85%, 5.18 to 0 meq / kg, 27.51 to 2.28 meq / kg, and 37.88 to 2.28 meq / kg.Key word:bentonite, Catfish, belly fat, fish oil, refinned